Pengaruh Manajemen Modal Kerja Terhadap Profitabilitas Perusahaan Studi pada Perusahaan Farmasi yang Listing di Bursa Efek Indonesia (BEI) Tahun 2008-2012 - Chrisna Nur Sundari; Ubud Salim (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The objectives of this research is to know the influence of independent variables working capital, either partially or simultaneously toward profitability in pharmaceutical firm on Indonesia Stocks Exchange during 2008 to 2012. This research uses quantitative approach with causal type, with 6 pharmaceutical firms listed in Indonesia Stocks Exchange. This research utilizes external data, those are taken from the website www.idx.co.id. Data which have already collected are processed with classic assumption test before hypothesis test. The statistic method that’s used in multiple regression analyze. The result of the reseacrh using t test that accounts payables have positive significant influence to return on assets, while Inventory and accounts receivables have no significant influence to return on assets. The result of the research simultantly using F test, shows that all of the three independent variables influence significant to return on assets. The coefficient determinant (R2) is 0.218 which means 21,8 % ROA variation explained by three independent variables, whereas 78,2% explained by another variables which is not followed. Keywords: Return on assets (ROA), working capital, accounts payables, accounts receivables, inventory